(untitled) (Bangladesh Journal of Pharmacology, 2019)
The study was devoted to see the effect of ethylmethylhydroxypyridine succinate, acetylcysteine and choline alphoscerate on the mitochondrial function under condition of experimental cerebral ischemia in rat. An integrated approach was used with the assessment of changes in the respirometric and antiapoptotic functions of mitochondria. It was found that the application of the objects under study contributed to a decrease in the intensity of glycolysis and the restoration of aerobic glucose metabolism with an increase in ATP synthesis, as well as a decrease in the dissociation of reactions in mitochondrial complexes I, II, IV and V. In addition, the introduction of the studied drugs reduced the intensity of caspase-dependent and caspase-independent apoptosis reactions, which, together with the restoration of mitochondrial respiratory function, contributed to the decrease in the size of the necrosis zone of the brain. Video Clip of Methodology: Rat middle cerebral artery occlusion: 8 min 7 sec Click to watch